Evaluation of the Effects of Spirulina platensis Extract on Productive Performance, Egg Quality and Serum Composition in Laying Japanese Quails Under Dexamethasone-induced Stress - Simin Bahrami; Bahman Parizadian Kavan; Heshmatollah Khosravinia; Babak Masouri; Mohsen Mohamadi Saei (Poultry Science Journal)
In a 3×2 factorial arrangement, the effects of dietary Spirulina platensis extract (0, 0.4 and 0.6 g/kg of diet) and dexamethasone (0 and 1 g/kg of diet) and their interactions were investigated on production performance, egg quality and hematological parameters in Japanese quails. A total of 150 laying Japanese quails, aged 8 wk, were divided into six treatments, five replicates with five birds each. Dietary dexamethasone supplementation decreased egg production, feed intake, egg weight and egg mass (p < 0.05). Moreover, the birds fed with dietary dexamethasone demonstrated a greater feed conversion ratio (FCR) compared to quails-fed diets without dexamethasone (p < 0.05). Dexamethasone treatment significantly also reduced shell thickness and yolk color in layer quail hens (p < 0.05). Supplemental Spirulina platensis extract significantly increased egg production, feed intake and egg mass (p < 0.05). Adding Spirulina platensis extract to the diet of laying Japanese quails improved the FCR compared to quails-fed diets without Spirulina platensis extract (p < 0.05). Spirulina platensis (0.4 g/kg of diet) added diets reduced serum triglyceride of the quails (p < 0.05). Eggshell thickness in quails fed on diets supplemented with Spirulina platensis extract was significantly greater compared to quails fed diets without Spirulina platensis extract (p < 0.05). The yolk color index in birds maintained on the diets supplemented with Spirulina platensis extract (0.4 and 0.6 g/kg of diet) was significantly greater than the birds fed diets without Spirulina platensis extract (p < 0.05). Based on the findings of the present research, the addition of dexamethasone (1 g/kg) to the diet of laying quails induced stress and also dietary supplementation of Spirulina platensis extract at 0.4 and 0.6 g/kg of diet improved egg production, egg mass, FCR, eggshell thickness and yolk color index.